2008
DOI: 10.1002/rra.1190
|View full text |Cite
|
Sign up to set email alerts
|

Does ice matter? Site fidelity and movements by Atlantic salmon (Salmo salar L.) parr during winter in a substrate enhanced river reach

Abstract: In-stream habitat enhancement is a common remedial action in rivers where degradation/lack of suitable fish habitat can be diagnosed. However, post-project monitoring to assess the response of the biota to modification is rare particularly during winter. We conducted in situ monitoring during the winters of [2004][2005][2006] in the regulated Dalåa River, central Norway, in order to determine if winter habitat requirements of Atlantic salmon (Salmo salar L.) parr were realized in an enhanced (substrate and mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Through the modifications of ice regimes, climate change will have a profound influence on the behavior and biological response of stream biota (Huusko et al 2007) and, therefore, will play a central role in their growth, survival and reproduction. Surface ice creates shelter habitats for fish in areas that are too exposed for use during open-water periods Linnansaari et al 2009). A reduction in such ice shelter will, therefore, lead to a loss of suitable winter habitat during the period when the water temperature has not yet reached the level to cause changes in fish habitat use.…”
Section: Lotic Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the modifications of ice regimes, climate change will have a profound influence on the behavior and biological response of stream biota (Huusko et al 2007) and, therefore, will play a central role in their growth, survival and reproduction. Surface ice creates shelter habitats for fish in areas that are too exposed for use during open-water periods Linnansaari et al 2009). A reduction in such ice shelter will, therefore, lead to a loss of suitable winter habitat during the period when the water temperature has not yet reached the level to cause changes in fish habitat use.…”
Section: Lotic Ecosystemsmentioning
confidence: 99%
“…Energy deficiency is important to winter survival, and a change in ice cover can reduce their ability to survive winter (Finstad et al 2004b). Movement of salmonids to overwintering habitats mostly occurs prior to ice formation in rivers; however, local movements between habitats also occur after ice formation (Jakober et al 1998;Linnansaari et al 2009). Extensive anchor ice precludes access, whereas patchy anchor ice and ice-covered areas appear to be preferred (Linnansaari et al 2009).…”
Section: Lotic Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to shelter in low embedded bottom substrates with stream wood is a key habitat factor for overwintering juvenile salmonids (Finstad et al, 2007;Stickler et al, 2008;Linnansaari et al, 2009), and in its absence, surface ice may provide overhead cover (Linnansaari et al, 2009;Watz et al, 2016). This study showed that, when denied access to winter shelter, juvenile brown trout display a stress response, mainly by increasing their ventilation frequency.…”
Section: Resultsmentioning
confidence: 78%
“…If ice is a case in climate change studies, the combination of changes in temperature and the current indexes of ice-induced flow changes could be used to assess future ice effects. Linnansaari et al [44] showed that ice had an effect on how Atlantic salmon utilized an artificial habitat in a regulated river, and unpublished data from the same river shows significant icedriven modification to the water level and thereby the function of the habitat in the same river. The Figure 8.…”
Section: Discussionmentioning
confidence: 99%